Design of Microstrip Patch Antenna at 10.3 GHz for X-Band Applications. Issue 1 (December 2020) - Sudhaman, K; Godhavari, T; Anusha, R
Abstract: In this study, an E shaped microstrip patch antenna is proposed. which is designed using FR4 - epoxy substrate. The designed antenna has a return loss of -29.21 dB and works with X band. The design is simulated using a software tool called HFSS (High Frequency Structure Simulator). The antenna has been designed for 10.3 GHz frequency applications and the return loss, VSWR and the radiation plot of the designed antenna has been evaluated. The aim is to achieve a high directivity with better gain and reduced losses particularly for X band applications.